Shakespeare's comedies of love : essays in honour of Alexander Leggatt - Knowles, Richard Paul, 1950-; Leggatt, Alexander; Bamford, Karen (University of Toronto Press, 2008)
Borrowing its title from renowned scholar Alexander Leggatt's landmark 1974 study, Shakespeare's Comedies of Love is a tribute to a critic who has shaped the way the world understands Shakespeare and his comedies. To help celebrate his distinguished career as a teacher and scholar, this collection of essays presents a wide range of new work on the Bard's comedies. The contributors cover diverse areas of inquiry, including the use of the comedies as a source of women's empowerment in nineteenth-century America; civic drama in Elizabethan London; male anxiety about women in the comedies; anti-Semitism in The Merchant of Venice; as well as some key productions of Shakespeare's comedies. Rich in detail and broad in scope, Shakespeare's Comedies of Love is a celebration of Leggatt's distinguished career, and an enduring collection of work on the world's most famous writer.